Making policy in turbulent times : challenges and prospects for higher education - Axelrod, Paul; Wellen, Richard; Shanahan, Theresa, 1963-; Trilokekar, Roopa Desai, 1963- (Queen's policy studies., 2013)
Can higher education policy-making be imaginatively theorized?